Increased antiviral capacity of transgenic silkworm via knockdown of multiple genes on Bombyx mori bidensovirus. (October 2018) - Sun, Qiang; Jiang, Liang; Guo, Huizhen; Xia, Fei; Wang, Bingbing; Wang, Yumei; Xia, Qingyou; Zhao, Ping
Abstract: Bombyx mori bidensovirus (BmBDV) causes fatal ﬂacherie disease leading to severe economic losses in sericultures. The BmDNV-Z genome contains two single-stranded DNA molecules, VD1 and VD2. For generating silkworm lines with antiviral properties, two transgenic RNA interference (RNAi) vectors were constructed. Open reading frames (ORFs) 1–4 of VD1 were knockdown by vector pb-BDV1 while ORF1a, ORF1b, and ORF3 of VD2 were knockdown by vector pb-BDV2. Transgenic silkworm lines BDV1-I and BDV2-I were generated via RNAi microinjection. Mortality rates of BDV1-I and BDV2-I were reduced by 45% and 39%, respectively, and quantitative PCR showed that VD1 and VD2 contents in BDV1-I and BDV2-I were signiﬁcantly lower than in the non-transgenic line. However, economic traits showed no obvious differences. Thus, knockdown of multiple BmDNV-Z genes provides strong resistance to BDV1-I and BDV2-I lines, and these can be used in sericulture without hampering silk production. Highlights: Transgenic silkworm lines were generated by silencing VD1 and VD2 genes of BmDNV-Z. Replication of VD1 and VD2 was suppressed in BDV1-I and BDV2-I, respectively. Mortalities of BDV1-I and BDV2-I were reduced by 45% and 39%, respectively. Economic characteristics of transgenic BDV1-I and BDV2-I were unaffected.